1998
DOI: 10.1017/s0033291797006065
|View full text |Cite
|
Sign up to set email alerts
|

Sex and depression

Abstract: Sex differences in rates of depressive disorder have not been convincingly explained, and this reflects a more general failure of research to provide a comprehensive aetiological account of depression. The difference can be used as a probe for evaluating the research base of integrative models of depressive disorder (e.g. Akiskal & McKinney, 1975). It is particularly likely to be illuminating if the causes of the sex difference do not overlap completely the causes of depression itself. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
5
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(106 citation statements)
references
References 88 publications
12
81
5
8
Order By: Relevance
“…Our study also showed that females have a greater risk of showing DS 6 months after stroke than males, in line with most studies. Similarly, this finding has been consistently reported in subjects without brain damage, but it remains unclear whether the determinants of this sex difference are biological or social [42]. We did not find a relation between the location of the lesion and the presence of DS after 6 to 10 months.…”
Section: Gms Nys Et Al / Journal Of the Neurological Sciences XX supporting
confidence: 79%
“…Our study also showed that females have a greater risk of showing DS 6 months after stroke than males, in line with most studies. Similarly, this finding has been consistently reported in subjects without brain damage, but it remains unclear whether the determinants of this sex difference are biological or social [42]. We did not find a relation between the location of the lesion and the presence of DS after 6 to 10 months.…”
Section: Gms Nys Et Al / Journal Of the Neurological Sciences XX supporting
confidence: 79%
“…According to the epidemiology of depression in the DSM-IV [42], depression is twice as frequent in females as in males. The present study showed that depression was 3.1 times more frequent in female ESRD patients than in male patients, and these patients were more likely to be depressed compared with subjects in a previous study [43]. …”
Section: Discussionsupporting
confidence: 50%
“…La relevancia de los roles sociales en las diferencias de género en depresión ha sido apuntada desde hace décadas (cfrs. Bebbington, 1998) habiéndose reconocido que tales diferencias aumentan en el periodo adulto cuando mujeres y hombres experimentan las desigualdad en estatus que conlleva el género (Mirowsky, 1996). El surgimiento de diferencias en depresión y autoestima entre mujeres y hombres en la adultez es una cuestión que debería analizarse en profundidad en posteriores trabajos, ya que dicho conocimiento puede ser útil para el diseño de políticas y programas que propicien mayor igualdad de género y mayor bienestar para la ciudadanía.…”
Section: Discussionunclassified